Biomechanical characteristics of knee flexion–extension in underwater situation. (1st January 2014) - Zhang, Weibing; Luo, Yin; Zheng, Jianyue; Graham, Michael
The purpose of this study was to observe the muscle activity and knee kinematics characteristics during the process of knee rehabilitation training. Ten healthy college students from sports institutions were recruited as subjects. Electromyographic (EMG) signals from quadriceps femoris and hamstrings were recorded during the task in which subjects were instructed to complete the motion of knee flexion and extension once and repetitively apart. The results showed that the EMG of the agonist muscle was activated and peaked before there was any motion of the knee. In the rehabilitation training mode, the knee angular velocity curve and peak value were similar. Collectively, these findings suggest that the single motion of knee flexion and extension is conducive to developing agonist strength.